Use of the guidelines directed medical therapy after coronary artery bypass graft surgery in Saudi Arabia - Khalid A. Alburikan; Rakan I. Nazer (Elsevier, 2017)
Background: incidence of cardiovascular diseases in Saudi Arabia is growing and more patients are expected to have cardiac revascularization surgery. Optimal pharmacotherapy management with Guideline Directed Medical Therapy (GDMT) post coronary artery bypass grafting (CABG) plays an important role in the prevention of adverse cardiovascular outcomes. The objective of this study was to assess the utilization of GDMT for secondary prevention in CABG patients and determine whether specific patients' characteristics can influence GDMT utilization. Method: A retrospective chart review of patients discharged from the hospital after CABG surgery from April 2015 to April 2016. The primary outcome was the utilization of secondary prevention GDMT after CABG surgery - aspirin, B-blockers, statin and angiotensin-converting enzyme inhibitors (ACEI) (or angiotensin receptor blockers (ARB) in ACEI-intolerant patients). The proportions of eligible and ideal patients who received treatment were calculated, and mixed-effects logistic regression was used to estimate odds ratios (OR) for the association of age, gender or patient nationality with the use of GDMT. Results: A total number of 119 patients included in the analysis. The median age of the cohort was 57.3 ± 11 years, and 83% were male (83.2%). Nearly 69.7% of patients had diabetes, and 82% had a previous diagnosis of hypertension. Nearly 91% received aspirin therapy and the rate was lower for B-blocker and statin. The rate of GDMT utilization did not change with the change in patient's age, gender or nationality. Conclusion: Despite adjustments for contraindications to GDMT, the rate of GDMT utilization was suboptimal.